Sistem Informasi Penjualan Furniture Berbasis Web Pada CV. Satria Hendra Jaya Pekanbaru - Yuda Irawan; Uci Rahmalisa; Refni Wahyuni; Yesica Devis (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
CV Satria Hendra jaya is a trading company engaged in the sale of furniture fixtures household appliances such as tables, chairs, cabinets, beds etc., where the promotion and sale is still conventional. This means that customers have to go to the CV Satria Hendra jaya to be able to purchase the product. Development of the e-commerce sales in the CV Satria Hendra jaya is an effort to increase sales and promotion of products that can benefit the company. The purpose of building an ecommerce sales of furniture, customers can order the products without having to come into the CV Satria Hendra jaya, the company was able to overcome the problem of product processing, booking processing thus providing convenience to consumers to get information about products CV Satria Hendra jaya. The system is built using PHP and MySQL database program and use the notepad ++ editor. The results of this research is to implement an e-commerce CV Satria Hendra jaya can be used as a sales promotion tool that can be accessed anywhere and anytime, the buying process can be directly without having to come to the store